Synthesis and molecular structure of pentadienyl complexes of the rare-earth metals12. Issue 41 (7th September 2018) - Raeder, Jan; Reiners, Matthias; Baumgarten, Robert; Münster, Katharina; Baabe, Dirk; Freytag, Matthias; Jones, Peter G.; Walter, Marc D.
Abstract : In combination with small and difficult to reduce rare-earth metals pdl′ undergoes CH-bond activations instead of sterically induced reductions to form dimeric complexes with a unique bridging six-membered metallacycle as the central structural motif. Abstract : The coordination chemistry of the sterically encumbered pentadienyl ligand pdl′ (pdl′ = 2, 4-(Me3 C)2 C5 H5 ) towards a series of rare-earth metals was systematically explored and the resulting metal complexes were fully characterized by several techniques including X-ray diffraction, elemental analysis, NMR spectroscopy and solid-state magnetic susceptibility studies. Three different reaction products were isolated depending on the redox-potentials and ionic radii of the metal atoms. They can be classified as (a) salt-metathesis, (b) metal reduction–ligand oxidation and (c) ligand deprotonation products. While for the larger and difficult to reduce metal ions, M = La, Ce, Pr and Nd, trivalent compounds [(η 5 -pdl′)3 M] (1-M ) were isolated, for the more readily reduced metal ions the corresponding divalent compounds [[(η 5 -pdl′)2 M(thf) n ] (2-M ; with M = Sm ( n = 2); Eu, Yb ( n = 1)) were formed. A more complex structural motif was observed for the smaller and also difficult to reduce metal ions, M = Sc, Y, Gd, Tb, Dy, Ho, Er, Tm and Lu, which yielded the bimetallic complexes of the type [(pdl′)(pdl′ −1H )(pdl′ −2H )M2 (thf)2 ] (3-M ). In these dimeric complexes the pdl′ ligand acts as a result of deprotonation reactions not only as a monoanionic [pdl′] −, but also as a dianionic [pdl′ −1H ] 2− and a trianionic [pdl′ −2H ] 3− ligand scaffold, which form unusual structural motifs including a six-membered metallacycle. Solid-state magnetic susceptibility studies revealed the expected free-ion magnetic moments at T = 300 K for all investigated compounds, whereas at lower temperatures crystal-field effects dominate. Furthermore, for3-Gd, 3-Tb, 3-Dy and3-Er weak ferromagnetic exchange interactions were observed at low temperature.